Pengaruh Filler Pada Pengelasan Tig Baja Karbon dan Stainless Steel 316l Terhadap Sifat Mekanik - Nurisna, Zuhri; Setiawan, Estu (Quantum Teknika : Jurnal Teknik Mesin Terapan, 2020)
In the manufacturing industry, the integration of different types of material is needed. The dissimilar metal welding of two different material were required suitable filler types. The often combination of material was done is welding between steel and stainless steel. TIG (Tungsten Inert Gas) welding process used feed electrode an electric arc. The gas around welding area has been protected the molten metal with outside air. This study aimed to determine the effect of selecting a suitable filler on the joining dissimilar metal beetwen SS316L and low carbon steel with the TIG welding method. The mechanical characteristics of ER316L and ER70S filler variations were testing by Tensile strength and microhardness vickers. The highest tensile strength and hardness value were found in the specimen welded by ER70S filler at 410 MPa and 398,1 HVN (Hardness Vickers Number). According to the study results, the ER70S filler is more suitable beetwen welding on the stainless steel and low carbon steel.